INTERAKSI KOMPOSISI MEDIA TANAM DAN ZAT PENGATUR TUMBUH (ZPT) ALAMI TERHADAP PERTUMBUHAN STEK LEMON (CITRUS LIMON L.) - WAYAN LANA; ANAK AGUNG GEDE PUTRA; NI PT EKA APRIASTUTI (GANEC SWARA, 2023)
This study aims to determine the effect of the composition of the growing media and natural growth regulators and their interactions on the growth of lemon cuttings. This research was conducted at Banjar Dinas Pangereregan Kaja, Lumbung Village, Selemadeg Barat District, Tabanan Regency. The altitude of the research site is 200 m above sea level. This research was conducted from 23 January 2022 to 20 March 2022 for 8 weeks from planting cuttings. The interaction  between the treatment of the composition of the planting medium  and the natural growth regulator had a very significant effect on almost all the variables observed, except for the variable plant height (cm) which had no significant effect  and plant diameter (cm) which had a significant effect . The highest total plant oven dry weight was obtained for the composition of manure media: soil : sand (1 : 2 : 1) and coconut water zpt  which was 5,22 g or an increase of 135,13% and the lowest was obtained in the treatment of the composition of manure media: soil: sand (1 : 2 : 1) and cow urine zpt  only 2,22 g. The highest total plant wet weight variable was found in the treatment of manure media composition: soil: sand (1 : 2 : 1) and shallot extract zpt which was 13,87 g or an increase in yield of 144,62% compared to the treatment of the composition of the manure planting medium: soil: sand (2 : 1 : 1) and shallot extract zpt  which gave the lowest total plant wet weight, which was only 5,67 g.